The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1080/09602010343000183
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of assets for virtual reality applications in neuropsychology

Abstract: Virtual reality (VR) technology offers new opportunities for the development of innovative neuropsychological assessment and rehabilitation tools. VR-based testing and training scenarios that would be difficult, if not impossible, to deliver using conventional neuropsychological methods are now being developed that take advantage of the assets available with VR technology. If empirical studies continue to demonstrate effectiveness, virtual environment applications could provide new options for targeting cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
261
0
9

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 390 publications
(280 citation statements)
references
References 56 publications
3
261
0
9
Order By: Relevance
“…An important question to explore for such application is to evaluate how spatial information is impacted when transferred from virtual to real environments. Several studies already found great results with disabled people about the question of spatial transfer [25][26] [27]. In this work, the authors agree that various factors can enhance this spatial transfer.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…An important question to explore for such application is to evaluate how spatial information is impacted when transferred from virtual to real environments. Several studies already found great results with disabled people about the question of spatial transfer [25][26] [27]. In this work, the authors agree that various factors can enhance this spatial transfer.…”
Section: Introductionsupporting
confidence: 70%
“…This device is also often adapted to the user's needs, notably for people with mobility issues. This the case with the elderly, patients with Parkinson's or Alzheimer's diseases, or sensorimotor injuries ( [25][26] [27]). Thus, clarifying the impact of joystick use represents a research challenge and is essential to resolve fundamental issues for clinical neuropsychological applications.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the environment can have stimuli and contingencies difficult to find in real world situations, thus providing exquisite control over characteristics of the environment such as geometry and size of the space and location of objects and features (like windows) within it. This ability to systematically vary environmental stimuli and contingencies should improve the analysis of spatial cognition [67] and spatial deficits. Thirdly, it is possible to test in virtual space multiple times for purposes of periodic assessment or practice and rehabilitation [23], a feature important for TBI survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Within that context, the present paper will summarize the ways that researchers and clinicians have employed VR to create relevant simulations that can be applied to the prevention, assessment, and treatment of PTSD. Some of the discussion in the current paper includes topics that have been discussed in previous papers, which may be consulted for deeper analysis (Rizzo et al, 2013; Rizzo, Buckwalter, & Neumann, 1997; Rizzo et al, 2010; Rizzo & Koenig, in press; Rizzo et al, 2017; Rizzo, Schultheis, Kerns, & Mateer, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…VR-based testing, training, and treatment approaches that would be difficult, if not impossible, to deliver using traditional methods have now been developed that take advantage of the assets available with VR technology (Rizzo et al, 2004; Rizzo & Koenig, in press). This unique match between VR technology assets and the needs of various clinical application areas has been recognized by a determined and expanding group of researchers and clinicians.…”
Section: Introductionmentioning
confidence: 99%